Safety and efficacy of osimertinib 160 mg daily given concurrently with a strong CYP3A4 inducer - Mostafa Aglan; Erin Spyropoulous; Joel Oster; Paul J. Hesketh; A.J. Piper-Vallillo (Respiratory Medicine Case Reports)
Introduction: Osimertinib remains the standard first-line therapy for patients with advanced EGFR-mutant NSCLC, at least in part due to its improved CNS penetrance compared to earlier generation EGFR TKIs. Strong CYP3A4-inducing medications are known to reduce the effective concentration of osimertinib, prompting the recommendation to double the standard osimertinib dose from 80 to 160 mg daily. However, little is known about the real-world safety and efficacy of osimertinib given in combination with long term CYP3A4 inducer use. We detail, to our knowledge, the first reported case of a patient receiving an escalated osimertinib dosage concurrent with a potent CYP3A4 inducer. Case presentation: A 69-year-old-female with a long-standing history of a seizure disorder was diagnosed with stage IV EGFR exon 19 deletion positive lung adenocarcinoma. After a failed trial to wean the patient off phenytoin, osimertinib at a dose of 160 mg in combination with phenytoin was recommended based on existing clinical guidelines. She achieved a partial response and continues with stable disease for more than 32 months from initiation of osimertinib. Additionally, she tolerated osimertinib well with minimal side effects although with persistent dyspnea of unclear etiology. Conclusion: Our case illustrates that 160 mg of osimertinib administered concurrently with a strong CYP3A4 inducer can be given safely and with retained efficacy in treating CNS metastatic EGFR-positive non-small cell lung cancer.